PENGARUH RUANG TUMBUH TERHADAP RESPON PERTUMBUHAN DAN PERKEMBANGAN TANAMAN MERANTI MERAH (Shorea pauciflora King.) DAN NYAWAI (Ficus variegata Blum.) - Adistina Fitriani (Jurnal Hutan Tropis, 2011)
The results showed that the arrangement of growing space T1, T2 and T1 + T2 combinations, each of which can increase the high growth 143.7% (172.30 cm), 37.1% (96.9 cm) and 105.7 % (145.40 cm), stem diameter width of 110.0% (18.30 mm), 34.7% (11.0 mm) and 123.3% (18.29 mm) and 142.6% canopy ( 181, 45 cm), 36.9% (102.4 cm) and 106.6% (154.55 cm) than the control (T0) to plant the meranti merah (Shorea stenoptera Burk.). The space to grow this type of Meranti merah (Shorea stenoptera King) Age 5 years have shown that treatment with a combination of vertical and horizontal (T3) showed best in order to enhance the growth of stem diameter, equal 118.2% (3.0 cm) than in the control (T0). The height of the plants in T1 and T2, and T3 have shown increased 55.6% growth, respectively at 133.3% and 66.7% compared to control (T0). Bandwidth test vintage Meranti merah (Shorea selanica Bl) cultivation of clippings from shoots in the treatment of broad lines of 2 m, 3 m and 4 m is still the original data (0 months) show a consistent altitude is 45.5 cm, 6 cm and 46, 47.7 cm. Growing requirements nyawai (Ficus variegata Blum.) In KHDTK Kintap in some areas with B-type, red soil climate yellow podzólicos (FA), the texture of sandy clay with drain if - so, solum shallow soil (< 50 cm) of depth (> 1 m), the pH of 4 to 5.5 soil with an elevation of 50 metres on the level of the sea - 433 meters of altitude in the Valley and the slope (flat topography - tracks (> 45%) on the State of the type of vegetation in the mix) rare density (natural vegetation). Tree species associated with nyawai (Duabanga moluccana), Macaranga spp, Shorea spp, Trema sp., and Anthocephalus cadamba. Related plant species are under cylindica grass, vines, shrubs, narrow leaved (leaves ribbon), among others, ferns, nettles and some types of grass.Keywords : growing space, growth, meranti merah,  nyawai